How useful is the carry-over effect for short-term economic forecasting? - Karl-Heinz Tödter (Deutsche Bundesbank, 2010)
The carry-over effect is the advance contribution of the old year to growth in the new year. Among practitioners the informative content of the carry-over effect for short-term forecasting is undisputed and is used routinely in economic forecasting. In this paper, the carry-over effect is analysed 'statistically' and it is shown how it reduces the uncertainty of short-term economic forecasts. This is followed by an empirical analysis of the carry-over effect using simple forecast models as well as Bundesbank and Consensus projections.
Keywords: C53; E37; C16; 330; forecast uncertainty; growth rates; carry-over effect; variance contribution; Chebyshev density; Konjunkturprognose; Prognoseverfahren; Wirtschaftswachstum; Schätzung; Deutschland